Calculation of time-dependent pressure under molecular flow using Monte Carlo method. (June 2015) - Zhang, Bo; Wang, Jie; Wei, Wei; Fan, Le; Pei, Xiangtao; Hong, Yuanzhi; Wang, Yong
Abstract: The Monte Carlo method can be used to study the time-dependent pressure in a vacuum system. In the usual simulation process, the test particles are traced and the locations of them are recorded at certain times, while they move and bounce in a vacuum chamber. So the particle numbers at some locations and moments can be obtained and then transformed into pressures using the ideal gas equation. A new method based on Monte Carlo is proposed in this paper. The locations and moments of the collisions between the particles and inner walls of chamber are calculated firstly, and then the locations of the particles at any other time are obtained by interpolation. For simplicity, pressure evolution in a pipe with rectangular cross section is simulated and presented to state this method. Highlights: A modification to usual Monte Carlo calculation of time-dependent pressure was proposed. Interpolation was applied to the calculation and pressure at any time can be obtained. 3D pressure distribution in a vacuum chamber was calculated and displayed.